(untitled) (The Science Post, 2025)
Heart disease continues to be the leading cause of death globally, claiming millions of lives each year. In response, the healthcare industry has embraced technological innovations to improve the detection, management, and treatment of cardiovascular conditions. From wearable devices to artificial intelligence and mobile health platforms, these technologies are transforming how heart disease is diagnosed and monitored. This paper discusses some of the most impactful technologies currently shaping cardiology, including wearable health monitors, AI-driven diagnostic tools, and telemedicine. It evaluates their real-world applications, benefits, and limitations, and considers how they might evolve to form the foundation of a more proactive and personalized cardiac care system.